Zn segregation in interface between Mg17Al12 precipitate and Mg matrix in Mg–Al–Zn alloys. (1st April 2019) - Liu, C.Q.; Chen, H.W.; Wilson, N.C.; Nie, J.F.
Abstract: The interface between continuous Mg17 Al12 precipitate and the Mg matrix in Mg–9Al–3Zn alloy has been characterized using aberration-corrected scanning transmission electron microscopy. It is found that Zn segregation occurs in the partially-coherent interface that is parallel to the basal plane of the Mg matrix and contains an array of misfit dislocations. The segregated Zn atoms substitute for the Al atoms within the interface and the segregation is not affected by the presence of the misfit dislocations. First-principles calculations suggest that Zn segregation is energetically favored. Graphical abstract: Unlabelled Image